PENGARUH MODEL SQ3R TERHADAP KEMAMPUAN MEMBACA KRITIS TEKS FABEL SISWA KELAS V SD - Rohmaniatul Hidayah, Syifa; Suhandi Saputra, Dudu; Mahpudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical reading ability is an essential skill that should be developed in elementary school, particularly in understanding fable texts that are rich in conflict, cause-and-effect relationships, and moral messages. Reading instruction, however, has generally remained focused on literal comprehension, so students' ability to interpret, analyze, and evaluate texts has not developed optimally. This study aims to determine the effect of the SQ3R model (Survey, Question, Read, Recite, Review) on the critical reading ability of fifth-grade students on fable texts. The study used a quasi-experimental method with a non-equivalent control group design, involving 44 fifth-grade students of SDN Cigasong 1 divided into an experimental class (SQ3R model) and a control class (Direct Instruction model), each consisting of 22 students. Data were collected through multiple-choice and essay tests and analyzed using the Paired Sample t-Test and Independent Sample t-Test with IBM SPSS Statistics version 30. The results show that the experimental class's pretest mean score of 54.27 increased to 86.86 on the posttest, while the control class only increased from 48.68 to 51.59. The Paired Sample t-Test produced a significance value of 0.000 (< 0.05), indicating a significant effect of the SQ3R model on critical reading ability. The Independent Sample t-Test also showed a significance value of 0.000 (< 0.05), confirming a significant difference between the experimental and control classes. Thus, the SQ3R model proved more effective than the Direct Instruction model in improving fifth-grade students' critical reading ability on fable texts.